Answer:
Explanation:
6cos^2(x) + 7cos(x) +2 = 0
Call cos(x) = y to change this to something a little bit more familiar.
6y^2 + 7y + 2 =0
This equation is a quadratic. Solve it first. Then we'll go back to solving for cos(x)
This equation factors into 2 possible answers
(3y + 2)(2y + 1) = 0
3y + 2 = 0
3y = - 2
y = - 2/3
2y + 1 = 0
2y = - 1
y = - 1/2
Now let's start with
cos(x) = - 1/2
That means that x is in quadrant two or three.
cos-1(1/2) = 60 degrees.
Quad 2: x = 180 - 60 = 120
Quad 3: x = 180 + 60 = 240
Now cos(x) = - 2/3
cos-1(2/3) = 48.19
Quad 2: x = 180 - 48.19 = 131.81
Quad 3: x = 180 + 48.19 = 228.19